A genome-wide scan in families with maturity-onset diabetes of the young: evidence for further genetic heterogeneity. - Frayling, T; Lindgren, C; Chevre, J; Menzel, S; Wishart, M; Benmezroua, Y; Brown, A; Evans, J; Rao, P; Dina, C; Lecoeur, C; Kanninen, T; et al. (2003)
Maturity-onset diabetes of the young (MODY) is a heterogeneous single gene disorder characterized by non-insulin-dependent diabetes, an early onset and autosomal dominant inheritance. Mutations in six genes have been shown to cause MODY. Approximately 15-20% of families fitting MODY criteria do not have mutations in any of the known genes. These families provide a rich resource for the identification of new MODY genes. This will potentially enable further dissection of clinical heterogeneity and bring new insights into mechanisms of beta-cell dysfunction. To facilitate the identification of novel MODY loci, we combined the results from three genome-wide scans on a total of 23 families fitting MODY criteria. We used both a strict parametric model of inheritance with heterogeneity and a model-free analysis. We did not identify any single novel locus but provided putative evidence for linkage to chromosomes 6 (nonparametric linkage [NPL]score 2.12 at 71 cM) and 10 (NPL score 1.88 at 169-175 cM), and to chromosomes 3 (heterogeneity LOD [HLOD] score 1.27 at 124 cM) and 5 (HLOD score 1.22 at 175 cM) in 14 more strictly defined families. Our results provide evidence for further heterogeneity in MODY.